A study of knowledge about solar radiation and sun protection among adolescents and young adults in Poland - Anna Szabrańska; Monika Zach-Źródlak; Natalia Rektor; Paulina Bronst; Lidia Rosa; Aleksandra Małolepsza; Magdalena Mazur; Klaudia Kister; Julia Czechowska; Jakub Laskowski (Kazimierz Wielki University, 2023)
Introduction Solar radiation plays an important role in many biological processes of the body. It is necessary for the production of cholecalciferol (vitamin D3) in the human body, which plays an essential role in maintaining bone and immune system function. Excessive and inappropriate exposure, however, can lead to serious health effects, especially when it comes to the skin. Knowledge about sun protection and the effects of solar radiation among young adults plays a key role in promoting a healthy lifestyle and cancer prevention. Objective The study aimed to assess the knowledge, attitudes, and behaviour of adolescents and young adults about solar radiation and sun protection. Materials and methods This study was conducted among 194 people from Poland, aged 15 to 30, consisting of adolescents and young adults. A specially developed original questionnaire was used to collect the data on knowledge about solar radiation, sun protection, and the use of creams with SPF filter. Results The study group included 117 (60.3%) women and 77 (39,7%) men. The average age of the respondents was 22,8 ±3,83 years. Most respondents are aware of the need to use sunscreen, but the frequency of use depends mainly on the season ( 34.3% always use sunscreen, and 40.4% use it mainly in the summer). There is a group of people (16.3%) who declare that they never use sun protect cream. According to the results, only a small group of respondents (7.2%) gave correct answers to all the questions and some people (6.2%) did not answer any of the questions. Conclusions The study shows the need for further efforts to increase the young people's knowledge and awareness of sun protection and to promote healthy habits in the use of SPF sunscreen.